1999
DOI: 10.1046/j.1442-2042.1999.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of prostate cancer detection by prostate‐specific antigen‐related parameters

Abstract: Background: The diagnostic value of prostate-specific antigen (PSA) for differentiating prostate cancer from benign prostatic conditions is limited by its lack of specificity. Several PSA-related parameters have been suggested as enhancing the discriminatory power of total PSA values, but their clinical utility should be considered preliminary until established in a prospectively evaluated cohort. Methods:In a prospective cohort study, results of ultrasound-guided biopsy and/or transurethral resection of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Our results support those of Egawa et al 5 emphasizing that the usefulness of both PSAD and PSATZD was similar in cancer detection for the patients with intermediate PSA levels. Furthermore, our results suggest that both PV and TZV also have significant predictive values as well as both PSAD and PSATZD in the ROC curve analysis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results support those of Egawa et al 5 emphasizing that the usefulness of both PSAD and PSATZD was similar in cancer detection for the patients with intermediate PSA levels. Furthermore, our results suggest that both PV and TZV also have significant predictive values as well as both PSAD and PSATZD in the ROC curve analysis.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3][4][5][6][7][8][9][10][11] Regarding the volume- Volume-adjusted PSA N Tanaka et al adjusted parameters, PSAD and PSATZD were considered as significant predictive factors. Kikuchi et al 7 reported that PSATZD has the most useful validity among PSA, free PSA to total PSA ratio, alpha-1-antichymotripsin-PSA complex, PSAD and PSATZD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17,[22][23][24][25][26][27][28][29][30][31][32] Although most studies showed an advantage of using PSAD compared with PSA alone, only a few studies could demonstrate further a better performance of PSAD compared with %fPSA. [32][33][34] Two of those studies included relatively small numbers of patients (n ϭ 43 patients and n ϭ 105 patients). 33,34 The other, very recent study by Sakai et al 32 in 400 Japanese men demonstrated a better performance of PSAD and, surprisingly, tPSA compared with %fPSA.…”
mentioning
confidence: 99%